The effect of EU3+ ion doping concentration in Gd2O3 fine spherical particles - Pires, Ana Maria [UNESP]; Santos, M. F.; Davolos, Marian Rosaly [UNESP]; Stucchi, Elizabeth Berwerth [UNESP] (Elsevier B.V., 2002)
This work reports on the preparation of Gd2O3, cubic system, with spherical particles, narrow size distribution, whether or not doped with 1-5 at.% of Eu3+ and the influence of Eu3+ concentration on optical and morphological properties. Average diameter and size distribution particle analyses were performed for all samples from SEM results. Doped samples were also investigated by luminescence spectroscopy and emission kinetic measurements. All oxide samples present a particle average diameter distribution range from 110 to 150 nm and a decrease of particle average diameter with the presence of Eu3+. The particle size decrease is almost the same for all samples with different doping ion concentration. Therefore, the presence of doping ion may be inhibiting particle growth after the nucleation process. From spectroscopic studies, the doping ion distribution in the surface of oxide samples can be considered homogeneous because concentration quenching is not observed, as well as a significant difference among the calculated lifetime for each sample. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: gadolinium oxide; europium; luminescence